A Note on "Understanding Cultural Persistence and Change: A Replication of Giuliano and Nunn (2021)" - Paola Giuliano; Nathan Nunn (Institute for Replication (I4R), 2024)
This note addresses the questions, concerns, and issues raised in "Understanding cultural persistence and change: a replication of Giuliano and Nunn (2021)." In terms of replicability, all of the tables in Giuliano and Nunn (2021) are correct, and the replication files match the output reported in the tables. In their note, the authors suggest alternative, more-restricted samples (e.g., omitting observations: under five years of age, under 16 years of age, living in rural locations, first or second-generation immigrants, with unmarried spouses, from specific ancestral groups, from the 1930 Census, etc.) and also less-restrictive samples (e.g., including grandchildren in analyses of parent-to-child cultural transmission for households that comprise three generations). We re-explain the logic of our baseline samples and why these samples are the most natural, as well as discuss the issues, complications, and incorrect reasoning associated with the authors' suggested alternatives. We also show, reproducing all relevant tables in full for each alternative raised, that our conclusions do not depend on these decisions.
Keywords: 330